2020
DOI: 10.1183/13993003.02197-2020
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: interim guidance on rehabilitation in the hospital and post-hospital phase from a European Respiratory Society- and American Thoracic Society-coordinated international task force

Abstract: BackgroundPatients with COVID-19 or post-COVID-19 will most probably have a need for rehabilitation during and directly after the hospitalisation. Data on safety and efficacy are lacking. Healthcare professionals cannot wait for published randomised controlled trials before they can start these rehabilitative interventions in daily clinical practice, as the number of post-COVID-19 patients increases rapidly. The Convergence of Opinion on Recommendations and Evidence process was used to make interim recommendat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
350
0
60

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 346 publications
(422 citation statements)
references
References 62 publications
12
350
0
60
Order By: Relevance
“…It is noteworthy that the International Task Force made no suggestion for or against routine referral for pulmonary rehabilitation, pulmonary function testing, or mental health testing within 30-60 days after discharge despite an ERS/ATS Task Force on pulmonary rehabilitation making suggestions in favour of these actions within 6-8 weeks in a recently published report that used similar methods [92]. In studies that validated the CORE process, the rare discordant recommendations were typically attributable to different panels with varying interpretations of scarce or low quality evidence [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the International Task Force made no suggestion for or against routine referral for pulmonary rehabilitation, pulmonary function testing, or mental health testing within 30-60 days after discharge despite an ERS/ATS Task Force on pulmonary rehabilitation making suggestions in favour of these actions within 6-8 weeks in a recently published report that used similar methods [92]. In studies that validated the CORE process, the rare discordant recommendations were typically attributable to different panels with varying interpretations of scarce or low quality evidence [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…For patients who are recovering from longer intensive care unit (ICU) stays and who may present with post-ICU syndrome [14], more intensive face-to-face rehabilitation may be required. A recent guideline provides expert consensus around rehabilitation, including a suggested core set of outcomes for people recovering from COVID-19 and this should be referred to when planning future COVID-19 rehabilitation programmes [2]. This is a single-centre report and the number of cases is limited; however, the case series indicates that rehabilitation via telehealth for people recovering from COVID-19 is feasible and safe when provided by experienced PR clinicians.…”
Section: Discussionmentioning
confidence: 99%
“…In the Australian healthcare context, it is early days in our understanding of the short and longer term rehabilitation needs of those recovering from coronavirus disease 2019 (COVID-19) (novel coronavirus SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2)). There is strong evidence for the efficacy of pulmonary rehabilitation (PR) for people with chronic respiratory disease [1] and previous literature has also demonstrated the benefits of PR in terms of improvements in exercise capacity and quality of life in survivors of adult respiratory distress syndrome and influenza A (H1N1) pneumonitis [2]. International statements have now suggested that the PR setting may be an appropriate rehabilitation pathway for patients recovering from COVID-19 who have persistent pulmonary and extra-pulmonary symptoms and functional limitations [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The next questions address post-hospital follow-up and referral for rehabilitation. Interestingly, this topic was also tackled in a previously published ERS/ATS coordinated Task Force using the same methodology [21]. For both Task Forces, the number of voters was above 90.…”
mentioning
confidence: 97%
“…For both Task Forces, the number of voters was above 90. Despite being released within a short period of time and using similar methods, some apparent discrepancies can be identified in these documents: the ATS/ERS coordinated taskforce on COVID-19 management published in this issue of the ERR could not make any recommendation on post-hospital respiratory follow-up and rehabilitation due to lack of consensus, while the ERS/ATS coordinated Task Force on rehabilitation suggested that "patients with COVID-19 should have a formal assessment of physical and emotional functioning at 6-8 weeks following discharge, to identify unmet rehabilitation needs" [21]. In addition, this Task Force suggested that "follow up of a hospitalised patient with COVID-19 should include measures of respiratory function and exercise-capacity at 6-8 weeks following hospital discharge" [21].…”
mentioning
confidence: 99%